PELAKSANAAN TUGAS TELEPHONE OPERATOR DI HARRIS RESORT BARELANG BATAM - Esrawati, Lidya; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Batam city is one of the cities that has a variety of interisting natural tourism potential. To support the development of tourism pontential. To support the development of tourism, the industry in terms of accomodation is increasingly important, but only professional players can compete, namely HARRIS Resort Barelang Batam. To improve the image of this resort, each department must have a perfect form of service. The first impression obtained by guests comes from the front office department, one of which is the telephone operator section which is a